2018
DOI: 10.1530/rep-17-0429
|View full text |Cite
|
Sign up to set email alerts
|

Removal of sialic acid from bull sperm decreases motility and mucus penetration ability but increases zona pellucida binding and polyspermic penetration in vitro

Abstract: This study tested the hypothesis that sperm sialic acid (Sia) is required to reach the site of fertilization, and that successful fertilization requires recognition of Sia from both the sperm and oocyte to occur. In addition, it has recently been reported that Siglecs (Sia-binding-immunoglobulin-like lectins) are present on the sperm surface. Thus, the possibility that the recognition of oocyte Sia was sperm-Siglec-mediated was also addressed. Sperm exposed to neuraminidase (NMase) exhibited lower overall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Similarly, a differential PNA binding has been associated with the fertility status of the HF and LF bulls, indicating the differential abundance of asialylated galactosyl (ß-1, 3) N-acetylgalactosamine in their spermatozoa ( 79 , 93 , 94 ). Likewise, a decrease in the sialic acid content from the cattle bulls was found to decrease the motility and the CMP ability, nevertheless, raised the incidence of polyspermic penetration of the eggs ( 19 , 77 ). A differential or probably anomalous spatial arrangement of O-linked and N-linked glycans, for example, those associated with the LF-SpAGT, is expected to render a distinct conformation on the spermatozoa of HF bulls.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Similarly, a differential PNA binding has been associated with the fertility status of the HF and LF bulls, indicating the differential abundance of asialylated galactosyl (ß-1, 3) N-acetylgalactosamine in their spermatozoa ( 79 , 93 , 94 ). Likewise, a decrease in the sialic acid content from the cattle bulls was found to decrease the motility and the CMP ability, nevertheless, raised the incidence of polyspermic penetration of the eggs ( 19 , 77 ). A differential or probably anomalous spatial arrangement of O-linked and N-linked glycans, for example, those associated with the LF-SpAGT, is expected to render a distinct conformation on the spermatozoa of HF bulls.…”
Section: Discussionmentioning
confidence: 93%
“…The glycoconjugates (GCs) of the glycocalyx are crucial components of several molecular mechanisms which underlie the regulation of interactions between the spermatozoa and the various cells and impediments encountered by the spermatozoa during its transit in the immunologic milieu, across the FRT ( 5 , 19 , 77 , 78 ). A spatial variation in the abundance of a variety of glycan moieties of the GCs was observed on the buffalo sperm surface in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yu et al (2018) proposed that phagocytosis in the female reproductive tract is mediated through L-selectin on leukocytes which binds sialic acid on the sperm surface, thus providing further evidence that the sperm sialome is correlated with spermatozoa survival within the female genital tract (Ma et al 2016). Recently our group demonstrated that while the removal of sialic acid from bull spermatozoa decreased motility and mucus penetration ability, its removal increased zona pellucida binding and polyspermic penetration in vitro (Fernandez-Fuertes et al 2018), thus providing further evidence of a key role in sperm transport prior to capacitation.…”
Section: Gene/breedmentioning
confidence: 90%